Utilizing Social Media as a Means of Memorizing the Qur'an - Milton Alan; Xuemin Pik; Arenaz Tania (Yayasan Adra Karima Hubbi, 2023)
Social media is a change from increasingly sophisticated technology. the influence of social media is very much in the community, the positive influence is one of which makes it easier to memorize the Al-Qur'an. Memorizing the Al-Quran is an action taken by someone to increase their memorization of reading without looking at the Al-Qur'an or text. Researchers conducted research at the Esa Unggul Integrated Islamic Elementary School in Pekanbaru. The purpose of the researchers in conducting this research was to find out how teachers apply social media as a means of memorizing the Qur'an for students at the Esa Unggul Integrated Islamic Elementary School, Pekanbaru. This school uses the wahdah method in memorizing the Qur'an. in this study the researcher used a descriptive method with a qualitative approach. techniques used by researchers in collecting data is by way of interviews, observation and documentation. The subjects in this study were school principals, teaching staff, and students. The results of research at the Esa Unggul Integrated Islamic Elementary School in Pekanbaru can be said to be effective, by using social media the students are very enthusiastic in memorizing the Qur'an. this is a new way to apply in schools. Here the teacher has its own challenges in using social media to serve as a means of memorizing the Qur'an. Because in general children use social media to play.